(untitled) (Mustansiria Dental Journal, 2005)
One hundred fort nine edentuolus atients who were included in this study seeking for a complete denture. Sixty five patients of them were seeking for a denture for the first time, 45 patients had a history of one set of denture, and 39 patients had a history of two sets of dentures. All the technical and the laboratory work for construction of the complete denture was followed under the supervision of one prosthodontist. The evaluation of the dentures regarding function, comfort, appearance and general satisfaction was done by the patients themselves. The results indicated that patients acceptability for wearing a new complete denture was increased in those with a histo of previous denture .